2018
DOI: 10.1177/0333102418776455
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate is more effective than acetazolamide at lowering intracranial pressure

Abstract: Background The management of idiopathic intracranial hypertension focuses on reducing intracranial pressure to preserve vision and reduce headaches. There is sparse evidence to support the use of some of the drugs commonly used to manage idiopathic intracranial hypertension, therefore we propose to evaluate the efficacy of these drugs at lowering intracranial pressure in healthy rats. Methods We measured intracranial pressure in female rats before and after subcutaneous administration of acetazolamide, topiram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 42 publications
5
77
0
Order By: Relevance
“…Treating elevated CSF secretion in IIH patients may be achieved through either serotonin to inhibit Na + -K + -ATPase pathway through the activation and phosphorylation of protein kinase C [33]; antisense thyroid transcription factor-1 oligodeoxynucleotide to reduce AQP1 mRNA and protein expression in the CP [34]; or acetazolamide and topiramate treatment [35] to decrease intracellular carbonic anhydrase CP epithelium [6]. However, reducing weight loss and inhibiting the actions of reproductive hormones as well as HC and may result in decreased CSF formation and ICP in IIH patients.…”
Section: Csf Secretionmentioning
confidence: 99%
“…Treating elevated CSF secretion in IIH patients may be achieved through either serotonin to inhibit Na + -K + -ATPase pathway through the activation and phosphorylation of protein kinase C [33]; antisense thyroid transcription factor-1 oligodeoxynucleotide to reduce AQP1 mRNA and protein expression in the CP [34]; or acetazolamide and topiramate treatment [35] to decrease intracellular carbonic anhydrase CP epithelium [6]. However, reducing weight loss and inhibiting the actions of reproductive hormones as well as HC and may result in decreased CSF formation and ICP in IIH patients.…”
Section: Csf Secretionmentioning
confidence: 99%
“…Although the carbonic anhydrase side effects are milder than with acetazolamide, it may cause cognitive slowing in a subset of patients. A recent study demonstrated topiramate to be more effective at lowering ICP than acetazolamide in healthy rodents 84 ; however, it is not known if this translates to humans.…”
Section: Medical Treatmentmentioning
confidence: 98%
“…Compared to placebo, acetazolamide did not significantly lower ICP over the same study period. 24 Human physiological studies would be further informative in assessing ICP levels in response to the common medications used. On the horizon may be more medical options, including 11β-Hydroxysteroid Dehydrogenase Type 1 inhibitors.…”
Section: Medical Management Of Iihmentioning
confidence: 99%